Pernikahan Dini Bagi Masyarakat Kampung Baru Desa Pitusunggu Kecamatan Ma’rang Kabupaten Pangkep Sulawesi Selatan - Said Syaripuddin; Ariesthina Laelah (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2021)
This study seeks to uncover the traditions of the Kampung Baru community who like to marry off their sons and daughters early. This paper is a qualitative-descriptive research with a phenomenological approach. Data collection is done by interview and observation. Data analysis in this study took place simultaneously with the data collection process. Data analysis was carried out through three stages of the water model, namely data reduction, presentation, and data verification. However, these three stages take place simultaneously, with the aim of providing accurate data and information for Ministry of Religion officials in formulating development policies in the field of religion. The research found that the practice of early marriage has been going on for a long time in Kampung Baru, and has even become a community culture that has been maintained for decades. The people of Kampung Baru view marriage as aiming to elevate one's sosial status. People's motivation for underage marriage is due to economic faktors, education, religion, and lack of legal awareness. In general, households built through underage marriages in Kampung Baru last quite long. The custom of the people of Kampung Baru to marry off their sons and daughters early needs special attention from all parties, especially the relevant government agencies, in order to provide enlightenment to the community about the risks and problems that can be caused to children and born generations.